Alternating Wetting and Moderate Drying Irrigation Promotes Phosphorus Uptake and Transport in Rice - Jiangyao Fu; Ying Liu; Yajun Zhang; Kuanyu Zhu; Junfei Gu; Zhiqin Wang; Weiyang Zhang; Jianchang Yang (Agronomy)
Despite the essential role of phosphorus (P) in rice growth, P-use efficiency (PUE) remains low due to limited bioavailable P in soils and an over-reliance on chemical fertilizers, leading to resource waste and environmental risks, such as eutrophication. This study investigates whether and how alternating wetting and moderate drying (AWMD) irrigation promotes P absorption and transport in rice. This study was conducted over two years using a pot experiment. Conventional flooding (CF) irrigation was applied throughout the growing season, while AWMD irrigation was imposed from two weeks after transplanting to one week before harvest. AWMD improved shoot biomass by 8.7–9.4% and the photosynthetic rate by 12–15%, significantly enhanced PUE, and optimized root traits and enzyme activities related to P uptake. It also promoted leaf acid phosphatase and ribonuclease activities, facilitating P remobilization to grains. In conclusion, AWMD enhanced the ability of roots to absorb P and optimized the redistribution of P between vegetative organs and grains, synergistically increasing grain yield and PUE in rice.